Reforms In The Higher Education System Of Uzbekistan: Problems Of Transformation - Siddikov, Ravshan Berdimuratovich (The journal of contemporary issues in business and government, 2021)
This article analyzes the trends of development of higher education in Uzbekistan in the context of globalization and the creation of modern higher education institutions, and also considers structural changes in this area as a result of gradual reforms. The participation of leading foreign universities and international organizations in advanced training and in the training of highly qualified personnel in Uzbekistan, is also viewed in the article. The causes of the emerged problems and the shortcomings in the development of higher education, including the training of highly qualified personnel, are reflected.